The principles of educational administration : their Islamic ethical dimension and implications for human resource development - Khalfan, Ali Salim (International Islamic University Malaysia, 1999)
The main objective of this study is to draw up Islamic ethical principles of educational administration from the Qur'an and the Prophet's Traditions (As Sunnah) and the Islamic legacy, especially those related to administrative practices. It aims at providding awareness of Iislamic ethics in educational administration and encouraging moral practices within educational institutions in order to improve educational leadership and human resource development. The employed an analytical qualitative method as its major methodology. Documentary analysis of the primary sources was conducted to explore and scrutinise some Islamic ethical principals of educational administration and to analyse their practical application in education and human resource development. The study argued that the incorporation of Islamic ethics within educational administration is necessary to enhance the effectiveness of an educational system and proper conduct of students and teacher trainees. It argued that the success of an educational process depends on the degree of ethical paractices found in the institution with co-operation of teachers, parents, and the community at large. It reinforces the belief that Islamic ethics and moral values could be instilled into students through religious teachings, courses on ethics, and practically by taking teachers and parents as the role model. The study identified several ethical values and qualities of educational leadership. These include sincerity, trustworthines, self-discipline, justice, diligence, teamwork spirit, preseverance, and loyalty to the organization, self-accountability, and commitment towards duty and responsibility. The study argued that Islamic principles of administrative practices are built upon Divine guidance. It identified some principles that have direc implications on educational administation and the achievement of educational goals. These are obedience to Allah, His messenger, and the authority, effective planning, mutial consultation (shura), effective communication, interpersonal relations, delegation of power and authority and cooperation towards a common pusuti of improving the educational process. The study argued that knowledge and ethics are vital to the successof educational process, human resource development, and the stability of eduational institutions. Ethics encourages administrators to place a right person in the right job in order to do justice and to ensure maximum achievement. It also safeguards employees from job stresses, apprehensions and uncertainties, and enhances employee's work performance. The research recommends among others, that educational administrators, authorities, teachers and parents should set good examples of ethial conduct and moral behaviour for children to emulate.